1994
DOI: 10.2175/wer.66.3.2
|View full text |Cite
|
Sign up to set email alerts
|

Constructed reed beds: A cost‐effective way to polish wastewater effluents for small communities

Abstract: This paper outlines the increasing need for effluent polishing in the United Kingdom. It puts that need in the context of the more than 700 sewage treatment works serving populations of less than 2 000 in Severn Trent Water's area of the English Midlands. Constructed reed beds have their place in a design selection matrix. At the end of 1991, they were in use at 12 sites and more than 60 are programmed for completion in 1992. The design and construction of reed beds used for effluent polishing is described. De… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0
1

Year Published

1996
1996
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(19 citation statements)
references
References 2 publications
0
18
0
1
Order By: Relevance
“…Such wetlands include "reed beds" and "root-zone" treatment methods [37] devised to obtained environmental duty from the macrophytes cultivated in trenches or on beds saturated with sewages or wastewaters. The wetland is normally a shallow bed, about 0.3 to 0.8 m deep, filled with layers of gravel (<15 mm) and sand (or sandy loam) of porosity around 42%.…”
Section: Summary Of the Technical Designmentioning
confidence: 99%
“…Such wetlands include "reed beds" and "root-zone" treatment methods [37] devised to obtained environmental duty from the macrophytes cultivated in trenches or on beds saturated with sewages or wastewaters. The wetland is normally a shallow bed, about 0.3 to 0.8 m deep, filled with layers of gravel (<15 mm) and sand (or sandy loam) of porosity around 42%.…”
Section: Summary Of the Technical Designmentioning
confidence: 99%
“…A welldesigned constructed wetland can achieve high removal efficiencies for contaminants, with low construction and operational costs when compared with traditional wastewater treatment methods (Brix, 1987;Conley et al, 1991;Green & Upton, 1994). However, greater understanding of the complex processes involved with higher plants, microorganisms, the soil matrix and pollutants in wastewater, and how they interact with each other within the wetland, is needed for further optimization of removal efficiency (Stottmeister et al, 2003;Thullen et al, 2005).…”
mentioning
confidence: 99%
“…Numerous reports have demonstrated that various macrophytes are effective in treating polluted water, including municipal waste water (Ge´rard, Jean-Luc, and Thierry 2002;Jing et al 2002), agricultural non-point source pollution (Headley, Huett, and Davison 2001;Millhollon et al 2009), and eutrophic water bodies (Green and Upton 1994). Macrophytes can take up nitrogen and phosphorus from surface water (Tanner 2001;Wang et al 2007), filter suspended particulate organic matter, increase the oxygen concentration of the water, and reduce flow velocity, which increases the water residence time.…”
Section: Nitrogen and Phosphorus Removal And Morphological And Physiomentioning
confidence: 99%